What happened in Cyprus - Orphanides, Athanasios (2013)
This policy letter sheds light on the economic and political backround in Cyprus and provides an analyses of the factors which lead to an intensification of the crisis there. It discusses the severe consequences of the errors made in the recent establishment of an adjustment program for Cyprus by the Europroup for European economic management as a whole.